Silent Sisterhood : Middle-class Women in the Victorian Home. - Branca, Patricia (Routledge library editions. Women's history., 2013)
This perceptive book studies the Victorian woman in the home and in the family. One of the central purposes is to rescue Victorian woman from the realm of myth where her life was spent in frivolous trifles and instead to show how she had a major part to play in the practical management of the home. The author makes judicious use of domestic manuals and other material written specifically for middle-class women. With statistical data to quantify the image as well, this book presents a better understanding of what it was like to be a middle-class woman in nineteenth-century England.